Efektivitas Penerapan Kaidah Imla’ Dasar dalam Memperbaiki ‎Kemampuan ‎Menulis Bahasa Arab Siswa ‎Kelas 7 MTsN 1 Kota ‎Malang‎ - Annisa, Isma (Tifani : Jurnal Penelitian dan Pengabdian Kepada Masyarakat, 2023)
This research aims to review the effectiveness of applying basic imla' rules in ‎improving Arabic writing skills of 7th grade students of MTsN 1 Malang City. The ‎method is quasi-experiment with one organization pretest-posttest layout. The research‎ began with a pretest to measure students' initial abilities, followed by giving ‎treatment in the form of teaching basic imla' rules, and ended with a posttest to ‎evaluate learning outcomes. The results showed an increase in students' writing ‎ability after being given treatment. The average pretest score of 77 increased to 88 in ‎the posttest. Statistical analysis with t-test shows that the t-count value of 7.11 is ‎greater than the t-table of 2.06 at the 0.05 significance level. This indicates the effectiveness of the application of basic imla' rules to improving students' Arabic writing skills by findings significant differences in the results of student writing before and after treatment is given. It is hoped that the results of this research can be a consideration for Arabic educators to give more attention the important role of imla' rules in Arabic learning and practice it regularly in order to improve students' Arabic writing skills earlier.